Peran Madrasah Diniyah dalam Peningkatan Mutu Pendidikan di SMA Nurul Jadid - Muhammad Ainul Yaqin; Fahril Al Khozaini; Khoirul Anam (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One of the institutions in the Nurul Jadid boarding school, namely Nurul Jadid Senior High School (SMA NJ), is an institution under the auspices of the boarding school. In this institution, it not only prioritizes general sciences but also emphasizes religious lessons which are highly emphasized so that they can form noble students. the method used by the institution to implement change must be adjusted to the conditions of its human resources. To improve madrasah diniyah activities at Nurul Jadid High School, several strategies have been implemented. The madrasah diniah activities now change frequently, with the formal school divided into four days and the madrasah diniah school two days. Nurul Jadid High School offers various educational support facilities to its students. Many teachers are competent in their fields, academic support activities such as Madrsah Diniyah, extracurricular activities, student organizations, learning communities, sports teams and libraries. One of the objectives of Madrasa Diniyah aims to convey the basic teachings and principles of Islam to students. This involves learning the Quran, hadith, tafsir, aqidah (belief), fiqh (Islamic law), and Islamic history. The data collection techniques used by researchers are observation, interviews and documentation. Data analysis uses Data Reduction, Data Display and Data Verification. The data checking technique is carried out with a credibility test, this technique is used to check the data.